Patient and physician attitudes regarding risk and benefit in streamlined development programmes for antibacterial drugs: a qualitative analysis. Issue 11 (10th November 2016) - Holland, Thomas L; Mikita, Stephen; Bloom, Diane; Roberts, Jamie; McCall, Jonathan; Collyar, Deborah; Santiago, Jonas; Tiernan, Rosemary; Toerner, Joseph
Abstract : Objectives: To explore patient, caregiver and physician perceptions and attitudes regarding the balance of benefit and risk in using antibacterial drugs developed through streamlined development processes. Design: Semistructured focus groups and in-depth interviews were conducted to elicit perceptions and attitudes about the use of antibacterial drugs to treat multidrug-resistant infections. Participants were given background information about antibiotic resistance, streamlined drug development programmes and FDA drug approval processes. Audio recordings of focus groups/interviews were reviewed and quotes excerpted and categorised to identify key themes. Participants: Two primary stakeholder groups were engaged: one comprising caregivers, healthy persons and patients who had recovered from or were at risk of resistant infection (N=67; 11 focus groups); and one comprising physicians who treat resistant infections (N=23). Results: Responses from focus groups/interviews indicated widespread awareness among patients/caregivers and physicians of the seriousness of the problem of antibacterial resistance. Both groups were willing to accept a degree of uncertainty regarding the balance of risk and benefit in a new therapy where a serious unmet need exists, but also expressed a desire for rigorous monitoring and rapid, transparent reporting of safety/effectiveness data. Both groups wanted to ensure that >1 physician had input on whether to treat patients with antibiotics developed through a streamlined process. Some patients/caregivers unfamiliar with exigencies of critical care suggested a relatively large multidisciplinary team, while physicians believed individual expert consultations would be preferable. Both groups agreed that careful oversight and stewardship of antibacterial drugs are needed to ensure patient safety, preserve efficacy and prevent abuse. Conclusions: Groups comprising patients/caregivers and physicians were aware of serious issues posed by resistant infections and the lack of effective antibacterial drug therapies and shared a consensus that streamlined development programmes represent a necessary response to the resistance crisis, but one that requires enhanced safeguards and risk communication.